Improvement in mechanical and structural properties of poly(ethylene terephthalate) nanohybrid - Saxena D.; Rana D.; Bhoje Gowd E.; Maiti P. (My University, 2025)
The wide range of applicability of poly(ethylene terephthalate) (PET) in various fields such as packaging, automobile parts, sports and textile due to its transparent nature, light weight and mechanical properties creates strong case to enhance its mechanical properties. By embedding nanofillers and thereby improving the mechanical properties, this spectrum can further be widened. The effect of addition of nanofiller in terms of stress concentration is a crucial phenomenon to understand the mechanical property enhancement. The nanohybrids of poly(ethylene terephthalate) (PET) and organically modified nanoclay have been prepared through solution casting route to enhance the properties significantly without any trade-off of deteriorating other properties. The dispersion of nanoclays in the polymer matrix has been observed through TEM images. Good level of dispersion has been achieved in nanohybrids due to specific interactions between nanoclay and PET matrix explored through XRD and FTIR spectroscopic measurements. Thermal stability of the nanohybrids has been tested through TGA and DSC analyses. The mechanical properties have been tested and found to be enhanced in the presence of nanoclay with increasing filler concentrations. The modulus has been increased for nanohybrids up to 93%, while the optimum value of modulus and toughness has been observed at 4 wt% filler percentage. The improvement in mechanical properties has been predicted using different models for randomly dispersed filler and has been found to be fitted in acceptable range. The hardness of the nanohybrids has been tested using Vickers hardness test and is found to be increasing continuously with filler loading. The structural formations upon uniaxial stretching have been contemplated through two-dimensional small-angle X-ray scattering as well as through wide-angle XRD. The nanohybrids have shown short-range ordering on uniaxial stretching in comparison with pristine PET. Blob size has been found out using Debye–Bueche model and is found to be increased upon stretching the samples. The polymer nanohybrids have been prepared for the mechanical property improvement without imparting high brittleness for practical applications. The behavior of nanoclay on stretching the polymer nanohybrids has also been studied in detail. © 2019, Springer Nature Switzerland AG.